Về một phương pháp điều khiển cựu trị hội tụ nhanh - Mạnh, Nguyễn Văn (Journal of Computer Science and Cybernetics, 2016)
A very fast converging algorithm for extremal control systems is presented in this paper. The algorithm is called “Cleftover stepping in sequentially stretched space”. The paper describes the optimization algorithm as well as, a model of extremal control systems and results of experimental computation.